Characterization of Bed Agglomeration in Circulating Fluidized Bed Boilers: Influence of Coal Quality and Bed Material Interactions - Cahyo, Nur; Triasdian, Yayak; Busairi, Achmad; Rahmanta, Mujammil Asdhiyoga; Paryanto, Paryanto; Fajar TK, Berkah (ROTASI, 2025)
The utilization of coal in generating energy across the world is extremely popular due to its low cost. Otherwise, coal quality plays a significant role in other potential problems. Such an interaction between bed material and coal properties could lead to the formation of bed agglomeration, which melts in the CFB boiler of a power plant. The result shows that the majority of agglomeration samples were granular and dominated by round shapes, as observed visually. The EDX analysis shows that the three biggest elements in the agglomeration sample are oxygen, silica, and calcium. Meanwhile, XRD analysis reveals that the most reactive products were muscovite, albite, and dolomite compounds. They were composed of natrium in the range of 1.95–2.84%, silicon in the range of 20.2–21.16%, aluminium in the range of 13.05–15.46%, calcium in the range of 1.05–3.11%, and others. Therefore, several potential alternatives might be the best way to reduce the risk of agglomeration in a boiler. Including using additives like china clay and soils, especially those containing kaolin, and utilizing alternate bed materials. Another promising option to prevent this problem is to reduce the combustion temperature and replace bed material periodically.